A new method for rapid screening of seed vigority of cereals - Mansour Taghvaei (Open Journal of Plant Science - Peertechz Publications, 2023)
Seed deterioration is one of the major problems in agricultural production in arid and semi-arid regions. Seed deterioration reduces seed vigor and seedling establishment in the field. To introduce methods with sufficient sensitivity to more accurately determine the degree of grain deterioration, various methods have been developed under the conventional name of "vigor tests". This study aims to provide a rapid method for assessing seed vigor using the electrical conductivity test. The germination test and emergence test were performed in a completely randomized design with three replications. Treatments included the Tritipyrom line at 13 levels and seed deterioration at two levels. Germination percentage, emergence percentage, and electrical conductivity were significantly affected by seed deterioration. The highest electrical conductivity and the lowest electrical conductivity were respectively related to the lines of (Ka/b)(cr/b)F2 and (St/b)(Cr/b)F4. Although the lines are not significantly different in terms of germination and emergence percentage. Electrolyte leakage in aged seeds increased sharply in the first hours and then had a diminishing, after which it stopped and followed the logarithmic model, But the lines were different in terms of the slope of the first part of the graph (which was exponential).with its help, we can classify the lines or variety in terms of the amount of cell leakage, which indicates the amount of cell permeability. The highest (37.03) and lowest (29.01) slopes in the exponential part of the graph were related to the numbers (Ka/b)(cr/b)F2 and(St/b)(Cr/b)F4 line respectively. Therefore, by using a simple and quick four-hour electrical conductivity test, cultivars can be classified in terms of storage potential and early vigor.